COVID-19 microbiological and radiological diagnostics : Mikrobiološka i radiološka dijagnostika COVID-19 - Jeličić, Karlo (Array, 2021)
The purpose of this paper is to present SARS-CoV-2 diagnostic methods and their optimal implementation. The main routine microbiological diagnostic tools are molecular and serological methods. Sensitivity and utilisation of molecular methods is the best at the disease onset, while serological methods are the best if used at least 5-7 days after disease onset. Positive molecular test result (real-time polymerase chain reaction; RT-PCR) must be interpreted in the clinical presentation context. A sampling site for molecular analysis is based on disease severity; upper and lower respiratory tract samples are used for mild and severe presentations, respectively. Virus cultivation is the only method of proving the existence of a viable virus in a tissue sample, but due to the method complexity, it is not a part of a routine process. Ground glass opacities with or without reticular pattern and/or consolidation are typical findings for COVID-19 pneumonia. Multi-slice computerized tomography (MSCT) is a superior radiological method for performing X-ray of the chests.